THE PROCESS OF DEPOPULATION IN THE RURAL AREAS OF UKRAINE - Kuczabski, Aleksander; Michalski, Tomasz (Quaestiones Geographicae, 2013)
This study gives an analysis of the diversification of the demographic situation in the rural areas of Ukraine in the years 1992-2011 in a regional depiction (it corresponds to the NUTS 2 division applied in the European Union). The demographic situation of the rural population is undergoing increasingly distinct deterioration. It is the worst in central Ukraine and relatively the best in its western part. This is an effect of political, economic and social processes initiated in today’s Ukraine after World War One. It overlaps with negative effects of the processes of political transformation taking place in already independent Ukraine. The chances of improving the demographic situation in rural areas are rather slim and depend on two factors: (1) a fundamental change in the state policy towards the Ukrainian countryside and (2) overcoming a prolonged socio-economic crisis.